TINGGINYA DURASI SCREEN TIME BERHUBUNGAN DENGAN POLA KONSUMSI DAN PERILAKU MAKAN BALITA USIA 3-5 TAHUN DI JABODETABEK - Putri, Mayra; Humayrah, Wardina (Journal of Nutrition College, 2024)
ABSTRACTBackground:  Screen  time  is  time  spent  in  front  of  a  screen,  such  as  watching  TV  and  playing  on  a  mobile  phone.  High  screen  time  at  3-5  years  can  affect  consumption  patterns  and  eating  behavior.  Objectives:  To determine the relationship between screen time and consumption patterns and eating behavior in toddlers aged 3-5 years in Jabodetabek.Methods:  This study used a cross sectional study design measured by Google Form with 102 toddlers aged 3-5 years. The questionnaires used included: CEBQ (Children Eating Behavior Questionnaire), PFSQ (Parental Feeding Style Questionnaire) and SQ-FFQ (Semi Quantitative Food Frequency Questionnaire). Statistical tests used t-test and Spearman rank correlation test.Results:  There was no significant difference in the duration of eating with utensils between toddlers with housewives and toddlers with working mothers (>90 minutes/day). However, there was a significant difference (p=0.001) in the duration of meals without gadgets, with toddlers with working mothers eating about 8 minutes longer than toddlers with housewives. In general, the duration of toddlers' meals without gadgets was 60 minutes shorter than with gadgets. For both working mothers and housewives, there was a significant relationship between meal duration and screen time use on toddlers' eating behaviour in terms of slowness in eating (p = 0.047, r = 0.256) and emotional undereating (p = 0.001, 0.512). And there is a relationship between meal duration and screen time use on animal protein consumption (p=0.003, r=0.448).Conclusion:  The more screen time a toddler has, toddlers tend to have slow eating, reduced appetite, and consume more animal side dishes than other food groups.Keywords:  consumption  patterns;  eating  behavior; screen  time;  toddler  ABSTRAKLatar  belakang:  Screen  time  merupakan  waktu yang  dihabiskan  di  depan  layar  seperti  menonton  TV  dan  bermain  handphone.  Tingginya  screen  time  pada  usia  3-5  tahun  dapat  mempengaruhi  pola  konsumsi  dan  perilaku  makan.  Tujuan:  Penelitian  ini  bertujuan  untuk  mengetahui  hubungan  screen  time  terhadap  pola  konsumsi  dan  perilaku  makan  pada  balita  usia  3-5  tahun  di  Jabodetabek.  Metode:  Penelitian  ini  menggunakan  desain  cross  sectional  studi  yang  diukur  dengan  Google  Form  dengan 102 balita usia 3-5 tahun. Kuesioner yang digunakan antara lain: CEBQ (Children Eating Behavior Questionnaire), PFSQ (Parental Feeding Style Questionnaire) dan SQ-FFQ (Semi Quantitative Food Frequency Questionnaire). Uji statistik menggunakan   uji beda dan uji korelasi Rank Spearman.Hasil: Tidak ada perbedaan signifikan pada lama makan balita yang menggunakan gadget baik pada balita yang mempunyai ibu rumah tangga dan ibu bekerja (>90 menit/hari). Namun, terdapat perbedaan signifikan (p=0,001) pada durasi makan tanpa gadget. Balita dengan ibu bekerja makan sekitar 8 menit lebih lama dibandingkan dengan balita dengan ibu rumah tangga. Secara umum, lama makan balita tanpa gadget jauh lebih cepat selama 60 menit dibandingkan dengan gadget. Baik pada ibu bekerja maupun ibu rumah tangga, terdapat hubungan signifikan antara durasi makan dengan penggunaan screen time terhadap perilaku makan balita pada aspek slowness in eating (p= 0,047, r= 0,256) dan emotional undereating (p=0,001, 0,512). Terdapat hubungan antara durasi makan dengan penggunaan screen time terhadap konsumsi protein hewani (p=0,003, r=0,448).Simpulan:  Semakin  tinggi  penggunaan screen time balita maka balita cenderung berperilaku makan lambat dan kurang memiliki keinginan untuk makan, selain itu balita lebih banyak mengonsumsi/mengemil lauk hewani dibandingkan kelompok pangan lain.Kata  Kunci:  balita;  perilaku  makan;  pola  konsumsi;  screen  time